Ultrasound diagnostics: assessment of tumor thickness and depth of invasion in squamous cell carcinoma of the oral cavity - G. F. Allakhverdieva; E. L. Dronova; T. Yu. Danzanova; A. F. Bacev; M. B. Pak; F. Sh. Kamolova (Опухоли головы и шеи, 2024)
Aim. To evaluate the capabilities of ultrasound using various approaches in determining the depth of invasion of squamous cell carcinoma of the oral cavity and to compare the results obtained with data obtained by the use of other diagnostic methods.   Materials and methods. In our reserch, ultrasonography was performed on 193 patients with primary malignant tumors of the mobile part of the tongue, floor of the oral cavity and tumors of rare locations (mucous membranes of the lip, cheek, alveolar processes). The age of the patients ranged from 15 to 85 years. In all patients, tumors were squamous cell carcinoma. ultrasound was performed using submandibular, intraoral and transbuccal approaches. ultrasonic data were compared with the results of pathomorphological examination, as well as of X-ray computed tomography and of magnetic resonance imaging with contrast.   Results. A statistically significantly high correlation was obtained for all ultrasound approaches (submandibular, intraoral and transbuccal) with the depth of invasion of the oral tumor determined pathomorphologically (r = 0.78; r = 0.89; r = 0.93; p <0.001). Ultrasound using all approaches shows statistically significantly better results in determining the thickness of tumorsof the tongue and mouth floor in comparison with X-ray computed tomography and magnetic resonance imaging (p <0.001). All diagnostic methods are characterized by an overestimation of the tumor invasion depth (overdiagnosis) as compared with pathomorphological examination. for exophytic tumors and oral cavity tumors of mixed growth with an exophytic component, the depth of invasion was less than the tumor thickness.   Conclusion. Ultrasound is an accessible, easily reproducible, radiation-free method, the resolution of which makes it possible to accurately determine not only the depth of invasion of oral tumors, but also the distance from the tumor to the midline of the tongue, that represents an important information when choosing the extent of surgical intervention.